Biosecurity implementation in poultry farms across Europe and neighboring countries: a systematic review - Vougat Ngom, Ronald; Leite, Marta; Tilli, Giuditta; Laconi, Andrea; Mahmood, Qamer; Prodanov-Radulović, Jasna; Allepuz, Alberto; Chantziaras, Ilias; Piccirillo, Alessandra (Frontiers in Veterinary Science, 2025)
IntroductionModern poultry production systems inherently concentrate large numbers of birds, which also increases the risk and potential impact of disease outbreaks. Biosecurity is widely recognized as the most important tool for reducing the risk of disease introduction, establishment, and spread to, within, and from an animal population. Thus, effective biosecurity is essential for sustainable poultry production, and assessing its implementation represents a crucial step. This systematic review aimed to evaluate biosecurity implementation in poultry farms across European and neighboring countriesMethodsThe Cochrane Handbook and PRISMA 2020 guidelines were followed to perform the systematic review.ResultsOf the 1,515 articles retrieved from four databases, only 44 met the inclusion criteria and 16 provided usable data for assessing biosecurity implementation. Despite relatively broad geographical coverage, including eight multi-country studies involving 36 national assessments, the distribution of studies was uneven. Moreover, most studies (77%) were pathogen- or disease-specific (e.g., Campylobacter spp., avian influenza, etc.) and focused on a single poultry species, primarily broilers (55%), while assessments involving minor poultry species were rare. There was also marked variability in the methods used to assess biosecurity, and the level of biosecurity implementation differed significantly across countries. Based on descriptive evaluations, 58% of farms implemented all the biosecurity measures assessed. According to scoring-based assessments, the overall average biosecurity score was 66.9 out of 100. The most frequently implemented measures were those related to infrastructure and control of biological vectors, disease management, and purchase of one-day-old chicks.DiscussionThe heterogeneity of results, driven by differences in study design, poultry species, production systems, and methodological approach, highlights the complexity of evaluating biosecurity across diverse national contexts. This variability may reflect differences in epidemiological conditions, research funding, and national priorities. Although this review focused solely on primary research studies, the findings underscore the need to promote cross-country collaboration to enhance knowledge sharing and data harmonization.